Hemophagocytic lymphohistiocytosis: a rare and fatal manifestation of dengue fever - Singla, Karan; Singh, Ajay; Sethi, Sameer; Datta, Priyankar K. (International Journal of Research in Medical Sciences, 2020)
Authors describe a rare case of dengue fever manifesting as hemophagocytic lymphohistiocytosis. A 26-year-old man presented with acute gastroenteritis along with high grade fever, leukopenia, thrombocytopenia, acute kidney injury, liver dysfunction. Further work-up revealed elevated serum ferritin and LDH levels, and bone marrow biopsy showed hemophagocytes. As dengue fever is in rising trend all over the world, especially in Asian countries, clinicians should look out for this rare but potentially fatal complication of dengue fever.